Locking plate osteosynthesis of scaphoid nonunion with severe bone defects: a case series - Welle, Kristian; Taeger, Stefan; Prangenberg, Christian; Hackenberg, Roslind Karolina; Kieback, Jan-Dirk; Kabir, Koroush (Scientific reports, 2022)
The treatment of scaphoid nonunion can be challenging with increasing defect size. We evaluated the outcome of scaphoid nonunion with a substantial bone defect treated with a multidirectional locking plate combined with cancellous bone grafting only. Thirteen patients with significant osseous defects measuring 6 mm or more suffering from primary nonunion without treatment (n = 6) or recalcitrant nonunion following Herbert screw osteosynthesis (n = 7) were treated and reviewed retrospectively. The stabilization was performed after debridement, autologous cancellous bone grafting and volar locking plate osteosynthesis. After a mean follow-up period of 12 months, 12 of the 13 patients achieved successful unions with a free range of motion and complete remittance of pain in everyday activity. The mean scapholunate angle decreased from 59.7° ± 11 to 43.9° ± 5 (effect strength d:1.7, p < 0.00001), scaphoid humpback deformity angle from 58.9° ± 8 to 45.1° ± 8 (d:1.8, p < 0.0001), whereas strength of the injured hand increased from 36.4 kg ± 10 to 42.4 kg ± 9 (d:1.4, p < 0.0001). One nonunion persisted without fragment dislocation receiving revision after 1 year. Thus, locking plate osteosynthesis with cancellous bone grafting is a valid alternative in scaphoid nonunions with extensive bone defects. Additionally, stable retention of the fragments prevents dislocation even in delayed or persistent nonunion. Further prospective studies are required to confirm these findings.